Magic Web and Other Stories - Debi, Ashapurna (New Delhi Orient Blackswan, 2012)
Debi, Ashapurna: Magic Web and Other Stories. New Delhi. Orient Blackswan, 2012. 9788125047087 Rs.395.00 --(823 D30M 118530)
Keywords: Indian Literature - bengali short stories; Widows Lives - short stories